Indole-3-acetic acid treatment promotes postharvest kiwifruit softening by regulating starch and cell wall metabolism - Guan, Wenhao; Cao, Mengze; Chen, Wei; Yang, Zhenfeng; Li, Xuewen; Wang, Li; Shi, Liyu (Frontiers in Plant Science, 2024)
The softening process of postharvest kiwifruit is a critical aspect of fruit quality that has been extensively studied. However, the impact of indole-3-acetic acid (IAA) treatment on this process remains largely unexplored. In this study, we examined the effect of IAA treatment on the softening of postharvest kiwifruit. The results depicted that kiwifruit treated with IAA exhibited decreased firmness and increased ethylene production. Treatment with IAA upregulated the expression of starch decomposition genes, including AcSEX and AcBAM, resulting in a reduction in starch content.Additionally, IAA treatment induced cell wall breakdown, attributed to the enhanced transcript levels of cell wall-related degradation genes such as AcPE, AcPG, AcPL, and AcCX compared to the control. Consequently, IAA-treated kiwifruit displayed lower levels of cellulose and protopectin but higher levels of water-soluble pectin. In summary, our findings indicate that exogenous IAA promoted postharvest starch and cell wall biodegradation in kiwifruit, which reduced fruit firmness and accelerated fruit softening.